The Psychoanalyst’s Money - Elvio Fachinelli (EJP import test, 2019)
Summary: The author stresses the extent to which analytic literature represses the issue of money and how its significance to the analytical relationship ought instead to be analyzed. Starting from a widespread fantasy among analysands, where the analyst is felt to be a prostitute, the author expands upon the limits of the analytical setting, which has been suffering from a sort of phobia of the gift since the days of Freud. To the concept of psychoanalysis “of the answering” by the analytical establishment, the author opposes a more living concept of “psychoanalysis of the questioning”. [1]
Keywords: " Psychoanalysis of the questioning" Analyst as Prostitute; Analytic Contract; Analytic Time; money